Synthesis of the Src SH2 domain and its application in bioassays for mirror-image screening. Issue 61 (7th August 2017) - Shu, Keitou; Noguchi, Taro; Honda, Kaori; Kondoh, Yasumitsu; Osada, Hiroyuki; Ohno, Hiroaki; Fujii, Nobutaka; Oishi, Shinya
Abstract : Mirror-image screening systems for Src SH2 domain inhibitors were established using a synthetic Src SH2 domain. Abstract : The Src SH2 domain was synthesized via native chemical ligation of two fragment peptides. The facile protocol was used to prepare the mirror-image SH2 domain (d -Src SH2 domain) and tetramethylrhodamine-labeled SH2 domains. The synthesized SH2 domains were correctly folded and showed activity, and using these proteins we established bioassays to identify novel Src SH2 domain inhibitors from an unexplored mirror-image library of natural products.